Investigation and Implementation of a 10 MHz DC/DC Converter For AESA Radar Applications - Hagman, Niklas; Gustavsson, Erik (My University, 2014)
The field of power electronics is under constant pursuit for devices with higher power density, improved efficiency, spectral purity, and low cost. In this thesis two DC/DC converter topologies converting 50 V to 30 V, with a maximum load of 6 W are implemented in hardware. The two converter topologies implemented are a Buck converter and a ZVS-CV converter. The converters suitability to operate with a switching frequency of 10 MHz is evaluated. The Buck converter showed an overall peak efficiency of 80.8 %, with a switching frequency of 9.8 MHz. The Buck output power stage alone showed a peak efficiency of 87.2 %. The ZVS-CV converter showed an overall peak efficiency of 76.1 % with a switching frequency of 9.0 MHz, and a peak output stage efficiency of 95.2 %. The higher efficiency for the output power stage of the ZVS-CV is a result of successful removal of switching losses in the switching transistor. The lower overall efficiency of the ZVS-CV converter is due to the need of a more complex control and driving circuit. However, it might be possible to improve the efficiency of the driver circuit in the ZVS-CV converter. The output voltage ripple in the Buck converter is approximately 500 mV compared to the 100 mV in the ZVS-CV converter. The ZVS-CV converter is deemed well suited for 10 MHz operation. Future work should include implementation of a voltage regulator, development of a more efficient driver and control circuit, adaptive control of the dead time and an improved output filter to increase voltage quality.
Keywords: Elkraftteknik; Electric power engineering